Analysis Of Determinants of Use Core Tax Administration System in 2025 Using the Unified Theory of Acceptance and Use of Technology 2 (Utaut2) Model - Al Farizi, Musyafa; Zulaika Putri Rokhimah; Kusuma, Septian Yudha; Wahyuni, Mirasanti; Adhi, Nurseto (Universitas Pamulang, 2026)
This study aims to analyze the success of the Core Tax Administration System (CTAS) information system from the taxpayer perspective using the UTAUT 2 model. The success of CTAS is crucial; if this tax service system is inadequate for taxpayers, it can reduce the system's adoption rate. The decline in CTAS use by taxpayers will have an impact on decreasing compliance levels, which will ultimately hinder state revenue receipts from the tax sector. The population in this study is the number of companies in Semarang City registered with the Semarang City Department of Industry and Trade (Disperindag) at the end of 2024, namely 845 companies. This study uses the Slovin sampling formula with a 5% error rate, resulting in a sample size of 271 companies. Therefore, the number of samples used in this study was 271 companies in Semarang City. Data were collected using questionnaires distributed to respondents through direct delivery and social media (Google Form). The results showed that Performance Expectancy, Social Influence, and Perceived Security have a positive and significant effect on Behavioral Intention. Furthermore, Facilitating Conditions and Behavioral Intention also had a positive and significant effect on Use Behavior. However, Effort Expectancy, Hedonic Motivation, and Price Value were not found to have a significant effect on Behavioral Intention.